2020
DOI: 10.1136/bmjdrc-2020-001243
|View full text |Cite
|
Sign up to set email alerts
|

Poorly controlled diabetes mellitus alters placental structure, efficiency, and plasticity

Abstract: IntroductionThe hemochorial placenta provides a critical barrier at the maternal–fetal interface to modulate maternal immune tolerance and enable gas and nutrient exchange between mother and conceptus. Pregnancy outcomes are adversely affected by diabetes mellitus; however, the effects of poorly controlled diabetes on placental formation, and subsequently fetal development, are not fully understood.Research design and methodsStreptozotocin was used to induce hyperglycemia in pregnant rats for the purpose of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Animal Care and Treatment Specifications. Holtzman Sprague-Dawley rats were obtained from Envigo and maintained in an environmentally controlled facility with lights on from 0600 to 2000 h with free access to food and water as described previously (53). Virgin female rats (age 8 to 10 wk) were mated with adult male rats (age >3 mo).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal Care and Treatment Specifications. Holtzman Sprague-Dawley rats were obtained from Envigo and maintained in an environmentally controlled facility with lights on from 0600 to 2000 h with free access to food and water as described previously (53). Virgin female rats (age 8 to 10 wk) were mated with adult male rats (age >3 mo).…”
Section: Methodsmentioning
confidence: 99%
“…Rat TS Cell Culture. Blastocyst-derived rat TS cells (54) were cultured in rat TS cell medium (RPMI 1640, 20% [vol/vol] fetal bovine serum [FBS]; Thermo Fisher Scientific), 100 μm 2-mercaptoethanol (M7522; Sigma-Aldrich), 1 mM sodium pyruvate (11360-070, Thermo Fisher Scientific), 50 μM penicillin (15140122, Thermo Fisher Scientific), and 50 U/mL streptomycin (15140122, Thermo Fisher Scientific) supplemented with 70% rat embryonic fibroblast conditioned medium prepared as described previously (53,54), fibroblast growth factor 4 (FGF4; 25 ng/mL, 100-31; Peprotech), and heparin (1 μg/mL, H3149; Sigma-Aldrich). For induction of differentiation, rat TS cells were cultured for 8 d in rat TS cell medium containing 1% (vol/vol) FBS and without FGF4 and heparin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Consequently and in consistent to various other research studies, 25 mM glucose was used in our study to simulate hyperglycemia observed in patients with diabetes. 33,34 It is also evident that type 2 diabetes type 2 diabetes is characterized by a chronic state of low-grade inflammation 35 and metabolic endotoxemia, where increased levels of LPS have commonly observed in patients with type 2 diabetes. 36,37 To replicate the chronic inflammation in ex vivo conditions, we used LPS concentration which has previously been shown to induce acute inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal glucose can cross the placenta ( 1 5 ) which, in turn, can send signals into the maternal and fetal circulations. The precise nature of these signals and their regulation in response to glucose changes are still unknown ( 6 ). In particular, the mechanisms underlying the regulator effects of hyperglycemia on placental development and growth have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%